Decadal Analysis of Research Trends in Statistical Literacy - Choudhary, Satyanarayan (International Research Journal of MMC, 2025)
This study critically examines the evolving landscape of statistical literacy research from 2015 to 2024 through bibliometric analysis of publication trends, co-authorship networks, co-citation patterns, and keyword clusters. Findings reveal a field marked by dynamic growth but persistent fragmentation, with publication output rebounding after early fluctuations to peak in 2024. While interdisciplinary connections between statistical literacy, healthcare, and education demonstrate strength, the analysis uncovers significant gaps in equity-focused research, representation of emerging scholars, and integration with modern data science paradigms. Co-citation networks highlight the dominance of established figures, suggesting systemic barriers to broader recognition, while keyword analysis reveals tensions between methodological rigor and practical application. The study identifies three key recommendations: fostering inclusive collaboration to amplify underrepresented voices, bridging theory and practice through innovative educational tools, and systematizing research agendas through standardized frameworks. These findings underscore the need for intentional strategies to ensure statistical literacy research remains relevant, equitable, and impactful in addressing contemporary data-driven challenges.